Corruption and managing the project cycle : the role of corrupt practices in NGO funding in Pakistan - Lehtonen, Petri (2013)
This Master’s thesis research explores the role of corrupt practices in development projects implemented by local NGOs in Pakistan. The intention is not to expose particular cases of corruption, but to study corruption risks and vulnerabilities in different phases of the project cycle and financial management (budgeting, accounting, financial reporting and auditing). It also explores other program support functions, i.e. procurement and human resources, and their vulnerability to corruption. The contribution of this study to academic literature is increasing awareness of NGO corruption and its different forms in Pakistan from the project management point of view. This is a qualitative study. The empirical data is collected by interviewing development experts in Pakistan. The data consists of six interviews and the purposive sampling method is used to select the respondents. The respondents form intentionally a heterogeneous group, who represent different embassies, international organizations and INGOs. The focused interview method is used. The empirical findings show various challenges related to corruption faced in NGO funding in Pakistan. Those include e.g. donors having limited access to the field, thus heavily relying on narrative and financial reporting; relying on audit reports in corruption detection despite the questionable quality of audit reports; common custom of overbudgeting and overestimating the required staff; and financial management is not being prioritized by either donors or implementing organizations. The study recognized that managing the projects is in many respects a balancing act in Pakistan, and recommends a wider distribution of financial information with beneficiaries as measure to increase transparency and downward accountability. Similarly, the donors are strongly encouraged to proactively share their projects’ financial information with other donors. It is also recommended to continue the research and further identify the best practices to prevent corruption in this particular context.